The Cost of Care for People With Chronic Kidney Disease - Braden Manns (Canadian Journal of Kidney Health and Disease, 2019)
Background: As the adverse clinical outcomes common in patients with chronic kidney disease (CKD) can be prevented or delayed, information on the cost of care across the spectrum of CKD can inform investments in CKD care. Objectives: To determine the cost of caring for patients with CKD who are not on dialysis or transplant at baseline. Design: Population-based cohort study using administrative health data. Setting: Alberta, Canada. Patients: Cohort of 219 641 adults with CKD categorized by estimated glomerular filtration rate (eGFR) between April 1, 2012, and March 31, 2014, into Kidney Disease: Improving Global Outcomes (KDIGO) CKD categories, excluding patients on dialysis or transplant at baseline. Measurements: The primary outcome was 1-year cumulative unadjusted health care costs, including the cost of drugs, physician visits, emergency department visits, outpatient procedures (including dialysis and other day medicine and surgery procedures), and hospitalizations for the year following each patient’s index date. Methods: Mean 1-year direct medical costs were estimated for the cohort as a whole and for patients in the different KDIGO CKD categories as defined at baseline. Costs were further categorized according to baseline demographic and clinical characteristics, and by type of care (ie, kidney care and cardiovascular care). Results: In 219 641 adults with CKD, the mean unadjusted cumulative 1-year cost of care was Can$14 634 per patient (median = Can$3672; Q1 = Can$1496, Q3 = Can$10 221). Costs were higher for those with more comorbidity, those with lower eGFR, and those with more severe albuminuria. The cost of kidney and cardiovascular care was Can$230 (1.6% of total costs) and Can$720 (4.9% of total costs), respectively, for the cohort overall. These costs increased substantially for patients with lower eGFR, averaging Can$14 169 (32.3% of total costs) and Can$2395 (5.5% of total costs) for kidney and cardiovascular care, respectively, for people with eGFR<15 mL/min/1.73 m 2 at baseline. Limitations: We only have estimates of the cost of health care for people with CKD, and not the costs borne by patients or their families. As we have not included costs for people without CKD in this analysis, we are unable to assess the incremental costs associated with CKD. Conclusions: We identified that patients with CKD, even when not on dialysis at baseline, had high health care costs (more than twice the cost per person in Canada in 2015), with a graded association between severity of CKD and costs. Our findings can inform current and future cost estimates across the spectrum of CKD, including an estimate of potential savings that might result from interventions that slow or prevent kidney disease.